Pharmacological Effects of Glycyrrhiza glabra L. as Antihepatitis and Hepatoprotective for Children - Faisal Akhmal Muslikh; Puja Adi Priatna; Wiwied Ekasari (Universitas Airlangga, 2023)
Background: The incidence of hepatitis in children has grown from the normal number of hepatitis cases since January 2022, and it will continue to rise since the etiology and pathophysiology are unknown. This case is distinct from those caused by the hepatitis A, B, C, D, and E viruses. Glycyrrhiza glabra L. is a medicinal herb that has long been used in medicine to treat respiratory, digestive, and immune system problems, but it is also known to have an inhibitory impact on the virus. Coronavirus-associated acute respiratory syndrome, hepatitis, herpes simplex virus, influenza virus. Objective: This article will look at Glycyrrhiza glabra L.'s antihepatitis and hepatoprotective properties. Methods: The Pubmed, Sage Journal, and Sciencedirect databases were searched using the Preferred Reporting Items for Systematic Reviews and Meta-Analyses (PRISMA) standards and the keywords